Characteristics of a Muslim Youth in the Qur'an Surah Yusuf, Verse 33, to Address Moral Decadence and the Free Lifestyle of Gen Z - Qaida, Muhammad Al; Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2023)
Several times, the word youth is mentioned in the Qur'an. Whenever the word youth is mentioned in the Qur'an, it is always accompanied by its nature and characteristics in this life. Youth is a time when humans are at their prime, but at this time, they will also be faced with social and moral problems. The Qur'an has explained how to be a good and great youth; from the many verses that explain youth, surah Yusuf verse 33 becomes the main verse that becomes a discussion and then turns to other verses that explain similar things. Youth from each generation have significant differences, especially those who have experienced the most changes following the rapid development of Generation Z, at the end of 2023 now, some of the early Generation Z have grown up to become youth, and the challenges of those who have become youth are not easy, the conditions of interaction and morals are also different from previous generations, So that there is a gap between their understanding and their parents or teachers who are mentors in the social life of the community. The Qur'an, as a guideline for all Muslims, must also be the main reference for young people in facing moral crises that are contrary to Qur'ani values because the Qur'an is an absolute guideline from God that can improve conditions anytime and anywhere, in this case, we can find out how to know the attitude and behavior towards moral crises for those who uphold Qur'ani values.